E-Waste and Harm to Vulnerable Populations: A Growing Global Problem - Heacock, Michelle; Kelly, Carol Bain; Asante, Kwadwo Ansong; Birnbaum, Linda S.; Bergman, Åke Lennart; Bruné, Marie-Noel; Buka, Irena; Carpenter, David O.; Chen, Aimin; Huo, Xia; Kamel, Mostafa; Landrigan, Philip J.; et al. (Environmental health perspectives, 2016)
Electronic waste (e-waste) is produced in staggering quantities, estimated globally to be 41.8 million tonnes in 2014. Informal e-waste recycling is a source of much-needed income in many low- to middle-income countries. However, its handling and disposal in underdeveloped countries is often unsafe and leads to contaminated environments. Rudimentary and uncontrolled processing methods often result in substantial harmful chemical exposures among vulnerable populations, including women and children. E-waste hazards have not yet received the attention they deserve in research and public health agendas. We provide an overview of the scale and health risks. We review international efforts concerned with environmental hazards, especially affecting children, as a preface to presenting next steps in addressing health issues stemming from the global e-waste problem. The e-waste problem has been building for decades. Increased observation of adverse health effects from e-waste sites calls for protecting human health and the environment from e-waste contamination. Even if e-waste exposure intervention and prevention efforts are implemented, legacy contamination will remain, necessitating increased awareness of e-waste as a major environmental health threat. Global, national, and local levels efforts must aim to create safe recycling operations that consider broad security issues for people who rely on e-waste processing for survival. Paramount to these efforts is reducing pregnant women and children's e-waste exposures to mitigate harmful health effects. With human environmental health in mind, novel dismantling methods and remediation technologies and intervention practices are needed to protect communities. Heacock M, Kelly CB, Asante KA, Birnbaum LS, Bergman AL, Bruné MN, Buka I, Carpenter DO, Chen A, Huo X, Kamel M, Landrigan PJ, Magalini F, Diaz-Barriga F, Neira M, Omar M, Pascale A, Ruchirawat M, Sly L, Sly PD, Van den Berg M, Suk WA. 2016. E-waste and harm to vulnerable populations: a growing global problem. Environ Health Perspect 124:550-555; http://dx.doi.org/10.1289/ehp.1509699.